Purification and characterization of three commercial phenylazoaniline disperse dyes. (2nd October 2017) - Umbuzeiro, Gisela A.; Szymczyk, Malgorzata; Li, Min; Chen, Yufei; Vendemiatti, Josiane A. S.; de Albuquerque, Anjaina F.; dos Santos, Amanda; Maselli, Bianca de S.; Kummrow, Fábio; Vinueza, Nelson R.; Freeman, Harold S.
Abstract : Although tons of disperse dyes are used worldwile, little information on their ecotoxicity is available. While in silico models can be used to predict their ecotoxicity, experimental results from Daphnia can show significantly higher toxicity than predicted. Thus the objective of this work was to extend the knowledge base in this area by evaluating the ecotoxicity of three widely used disperse dyes and comparing the results to predicted values. Bearing in mind that generating ecotoxicity data on azo disperse dyes is complicated because they are not readily found as homogeneous compounds, we employed chromatographic methods to purify three commercially dyes C.I. Disperse Violet 93, Blue 291, and Blue 373 already found in the aquatic environment. No acute toxicity was observed for Daphnia similis. These results seems to be in general agreement when compared with ECOSAR predicted values. We hypothesize that differences in Kow values could explain the variations in results.